Pengaruh Harga, Promosi, dan Ulasan Produk Terhadap Keputusan Pembelian Melalui Aplikasi Shopee - Ghofur Ainun Najib, Abdul; Noor Andriana, Ana (Jurnal Syntax Fusion, 2022)
Shopee's last five quarters were at the peak of popularity with the highest average web visitors of 103,645,340 starting from Q1 2020-Q1 2021, but at the point of Q1 2021 there was a decline of 1,920,800 which resulted in the shifting of Shopee to rank two after Tokopedia. The purpose of this study was to examine the effect of price, promotion, and product reviews on purchasing decisions through the Shopee application. SPSS statistics version 24 is a software used to help analyze data, namely multiple linear regression. The type of research used in this research is associative quantitative research which aims to determine the effect of two or more variables. Sampling in this study using purposive sampling technique with a total sample of 81 respondents. Data collection techniques using literature, observation, interviews, questionnaires and documentation. The hypothesis of this research is the influence of price, promotion, and product reviews on purchasing decisions through the Shopee application at the LDK Fisip Mulawarman University. The results of price analysis have no partial effect on purchasing decisions with the value of the results of the t test (X1) -1.511, and promotions and product reviews have a partially significant effect on purchasing decisions with the value of the t-test results (X2) 2.014 and (X3) 7.095, while the F of 19.403, thus price, promotion, and product reviews have a significant simultaneous effect on purchasing decisions.